(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Chanlabut U, Nahok B. 2022. Forest structure and carbon stock of Suan Phueng Nature Education Park in Ratchaburi Province, Western Thailand. Biodiversitas 23: 4314-4321. Forests play an important role in the global carbon budget. Yet, carbon stocks in tropical forests are uncertain depending on many factors. This study aims to study forest structures and carbon stocks in Suan Phueng Nature Education Park, Ratchaburi, Western Thailand. In 12 plots of 20 × 20 m, an inventory of trees ? 4.5 cm diameter at breast height (DBH) was carried out. Soil samples were also collected in sampling plots. To describe forest structures, ecological parameters were analyzed (IVI, diversity indices, basal area, and DBH size classes). Forest carbon stocks were calculated based on biomass and soils. Allometric equations were used to calculate aboveground biomass and converse to carbon stock. The soil carbon was analyzed using the wet oxidation method. The result showed that the lower montane forest (493.74 ± 90.20 Mg C ha-1) had the highest forest carbon stock, followed by the dry evergreen + mixed deciduous forest (203.83 ± 82.74 Mg C ha-1), and mixed deciduous forest (145.46 ± 47.90 Mg C ha–1). In the three forests, there were atotal of 637 trees belonging to 70 species in 29 families. Shannon’s diversity index was 3.59 with a range of 2.17-3.21, indicating a moderate to high diversity. Tree density was 1,137.50 stems ha-1 with a range of 737.50-1,581.25 stems ha-1. The basal area had a range of 5.82-11.11 m2 ha-1. The DBH classes exhibited J-shaped distribution. The large trees (?71 cm) had a greater aboveground carbon stock, despite their lower density. This indicates their importance as carbon sinks in the forest. This study highlights that the forests in Suan Phueng Nature Education Park not only have the potential to be carbon stocks but also contain a high diversity of tree species.